A quantitative analysis on the sentencing disparity in online romance scam cases in United States: a focal concern theory perspective - Wang, Fangzhou (Crime & delinquency, 2024)
An online romance scam occurs when a criminal creates a fake online identity to manipulate a victim into developing affection and trust before financially exploiting them. It has resulted in billions of dollars in losses globally, impacting victims financially emotionally. Based on focal concern theory, this study is the first to examine the fairness of sentencing for this group of scammers in the United States. The study quantitatively analyzes 148 sentencing cases, which is the current most comprehensive dataset available, obtained from Pacer Monitor. The findings indicate that sentencing outcomes for scammers in the United States are primarily influenced by legal considerations. A comparison with similar studies conducted in China shows a consistent overall conclusion, although there are slight differences in the specific legal factors that have an impact. This study contributes to academic literature by addressing a notable gap in research within Western countries. The application of focal concern theory provides additional contextual insights, enriching the current understanding of this complex issue. Recommendations include prioritizing international collaborations, conducting detailed assessments of victim numbers and defrauded amounts, and proposing specialized laws to address the complexities of online romance scams.